A POSITION OF HONOUR OR SHAME? YHWH AS AN ARMOUR BEARER IN PSALM 35:1-3 - L Sutton (Acta Theologica)
The imagery of a shield in the Psalms is applied to YHWH in many instances: from YHWH as the shield of salvation or as the shield of refuge, to the destroyer of the shield. In Psalm 35:2, YHWH takes on the position and duties of an armour bearer (or shield bearer) for the king. This article raises the question as to whether or not the position of armour bearer for the king is a position of honour or shame? To answer this question, the article evaluates the function and duties of an armour bearer from the context of honour and shame, using inter- and extra-textual sources.